Character Development and Deviant Behavior: A Systematic Review of Theft Among Students in Educational Environments - Priyanto, Firman; Mustofa, Triono Ali; Jinan, Mutohharun (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
In schools and colleges theft of students' property is a chronic problem that influences the formation of students' character and social activity. This is not only to the detriment of the quality of education, but it also undermines confidence between teachers and students and parents. So the purpose of this study is to rise over what induced stealing behavior, developing character students stolen acts and what institutions could do not be a person who likes to steal. The research employ method is a systematic literature review with qualitative approach reviewing and analyzing on character building, criminal behavior, and student theft. Searches for literature were made on international databases using the key words "deviant behavior", "theft", "character" and "students in education". The study found that stealing behavior was shaped by both internal elements (personality, self-esteem) and external phenomenon (peer influence, family factors; social injustice). This is not conducive to building good character in students, in particular on issues of honesty, responsibility and empathy. Schools can help to combat stealing by incorporating a character education program built on high morals of honesty, integrity and personal responsibility. In sum, students' stealing behavior is a personal moral issue as well as an indicator of the defected social environment and education condition waiting to be improved. Theoretical implications of the study reported above suggests that a multi level perspective (family, teacher and school) should be used to inspire an environment that’s conducive for character formation in students also to minimise stealing behavior.